IEEE 802.1x-based user identity-embedded IPv6 address generation scheme - Peng KUANG; Ying LIU; Lin HE; Gang REN (Dianxin kexue)
Embedding extensible user identities into IPv6 addresses not only provides the possibility of tracing the user identity and finely controlling the user behavior,but also helps to improve the security,auditability and credibility of the Internet.Current schemes that embed user identity within IPv6 address are hard to deploy in practice due to the complexity of DHCPv6 client development or the complicated management of temporary address.Considering the sequential logic between identity authentication and address allocation,a IEEE 802.1x-based user identity-embedded IPv6 address generation scheme was proposed.By conducting identity authentication using layer-2 mechanisms and then assigning IPv6 addresses,this scheme decoupled the process of identity authentication and address allocation,and avoided the limitation of developing new extended DHCPv6 clients for each operating system and maintaining temporary address leases on DHCPv6 servers,which was more deployable.